A METHOD FOR EVALUATION OF THE CHAIN DRIVE EFFICIENCY - Egorov, Aleksey; Kozlov, Konstantin; Belogusev, Vladimir (Journal of Applied Engineering Science, 2015)
This paper is devoted to the development of a method and instruments for evaluation of the efficiency of a electric chain drive in all possible modes of operation. The proposed method allows determining the torque and the efficiency of electric chain drives and evaluating their efficiency with a high measurement rate as it uses the acceleration time as the efficiency criterion. A new method requires a minimal amount of additional equipment and, therefore, is more cost-effective than existing methods. Based on the results obtained at experiments we can conclude the applicability of the developed method for evaluation of the electric chain drive efficiency and it can be fully used for the study and technical state control of electric chain drives.
Keywords: Chain transmision; Performances; Moment of inertia; Efficiency; Chain drive